2018
DOI: 10.1111/faf.12267
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte recruitment and fecundity type in fishes: Refining terms to reflect underlying processes and drivers

Abstract: Only with new technology and the ability to simulate systems are we beginning to understand fish reproductive processes at the individual scale over time. Traditionally, oocyte recruitment and fecundity type in fishes have been based on a “snapshot” approach, that is a histological micrograph and/or oocyte size frequency distribution of a spawning capable female has been assumed to indicate oocyte recruitment processes over time. This has important implications as the asynchronous and group‐synchronous oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 45 publications
(110 reference statements)
4
33
0
Order By: Relevance
“…The D cOvi values increased gradually in line with the stage of oocyte development ( i ) ( (Supporting Information Figure S6), this observation, together with the OSFD patterns ( Figure 3a) indicated that this species performs a discrete development of oocytes (Ganias & Lowerre-Barbieri, 2018).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The D cOvi values increased gradually in line with the stage of oocyte development ( i ) ( (Supporting Information Figure S6), this observation, together with the OSFD patterns ( Figure 3a) indicated that this species performs a discrete development of oocytes (Ganias & Lowerre-Barbieri, 2018).…”
Section: Resultsmentioning
confidence: 62%
“…The D cOv i values increased gradually in line with the stage of oocyte development ( i ) (Table ). Oocytes at different development stages were simultaneously present during different MATs (Supporting Information Figure S6), this observation, together with the OSFD patterns (Figure a) indicated that this species performs a discrete development of oocytes (Ganias & Lowerre‐Barbieri, ). As shown in Figure b, the L T ‐based O cN i of early secondary growth oocytes (CAO + VTO1) decreased after the peak of spawning activity was reached, suggesting that the standing stock of oocytes is not replaced after this point.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The lack of PG reserves in females with the most developed ovaries indicated that all PG oocytes had been recruited to the SG phase. Complete recruitment of PG oocytes to the SG phase characterises the semelparous life strategy (Ganias & Lowerre‐Barbieri, ). Thus, our result aligns with previous reports that allis shad in the Mondego River is mostly semelparous (Alexandrino, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we encountered difficulties when using this technique with G. morhua and found that the hiatus limits were not always clear (this study). Thus, the required stringency of fecundity style may certainly be problematic 11 when studying oocyte size frequency distributions (OSFDs).…”
mentioning
confidence: 99%